Influence of 6-benzylaminopurine and culture medium on the regeneration of axillary shoots of Psidium cattleyanum Sabine cultivars Ya-cy and Irapuã - Bico, Alexandre Klas; Degenhardt, Juliana; Ribas, Luciana Lopes Fortes (Revista Ceres, 2025)
Psidium cattleyanum, commonly known as araçá, is a fruit tree valued for its nutritional benefits and is increasingly consumed fresh and processed. However, the genetic variability within its populations makes selecting and propagating individuals with desirable traits challenging. This study aimed to optimize the in vitro shoot regeneration from axillary buds of Irapuã and Ya-cy cultivars using a complete MS culture medium and half-strength MS basal salts (MS/2), supplemented with 6-benzylaminopurine (BAP). Apical shoots from in vitro germinated plantlets were placed on MS or MS/2 medium, supplemented with 2.2, 4.4, or 8.8 µM BAP, and a control without BAP. For the Irapuã cultivar, the highest shoot regeneration rate was achieved on MS/2 medium with 2.2 µM BAP during the third subculture, resulting in 100% of the explants producing shoots. In contrast, the Ya-cy cultivar showed the best results on MS/2 medium with 4.4 µM BAP, yielding up to 78.3% shoot formation in the first subculture. Both cultivars were rooted on MS/2 culture medium without plant growth regulators, with cv. Irapuã achieving up to 100% rooting and cv. Ya-cy 41.2%. A micropropagation protocol was successfully developed for the Irapuã and Ya-cy cultivars.